Answer:
![t_n = 4n - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/pgq5wmedu3ajdjjtg1djqaqys0s8vcapdw.png)
===========================================
Work Shown:
The first term is a = 2 and the common difference is d = 4, since we're adding 4 to each term to get the next term.
![t_n = \text{nth term of arithmetic sequence}\\\\t_n = a+d(n-1)\\\\t_n = 2 + 4(n-1)\\\\t_n = 2 + 4n - 4\\\\t_n = 4n - 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/lanimzon9vh9u1rl6uwd5n785b12d6up5n.png)
Which is the answer.
--------------------------------
If you were to plug in say n = 3, then we get
![t_n = 4n - 2\\\\t_3 = 4(3) - 2\\\\t_3 = 12 - 2\\\\t_3 = 10](https://img.qammunity.org/2021/formulas/mathematics/high-school/9wn7xskh3u57vlhfpogyhysp1lyvz3jehi.png)
showing that 10 is the third term, which matches with what the original sequence shows. I'll let you check the other values of n to fully confirm the answer.